GE_GERICHTE P/3596/2018 vom 15. April 2019 - GE Cour de justice (2019)
BRIGANDAGE; VOL(DROIT PÉNAL) ; DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) ; PROFIL D'ADN ; ANTENNE ; INSTALLATION DE TÉLÉCOMMUNICATION | CP.139; CPP.81; CP.140; CP.144.al1